Allelopathic activity of Sida cordifolia L. methanol leaf extract on selected noxious weed species - Ahmed, Hassan (2018)
Growing concern regarding increase in herbicide resistance weed species due to extensive use of synthetic herbicides which promote soil contamination and pose pollution to our environment, hence, an alternative weed control strategy using natural herbicide was adopted. Sida cordifolia is a herb belonging to the family Malvaceae and grows throughout the tropical and sub-tropical regions. It invades and colonize a mass of land. The allelopathic effect of S. cordifolia leaf methanol extract were evaluated based on experiments conducted in laboratory, glasshouse and field condition to determine germination, growth, physiological and biochemical activity on weed plants namely O. sativa (weedy rice), A. conyzoides, A. gangetica, E. crus-galli, E. colona and P. hysterophorus. Sample of S. cordifolia was collected from wild area in Nigeria and prepared to powder. Extraction was conducted using 100 g of S. cordifolia leaf powder into 2 litres 70% methanol. Concentration levels were prepared from stock to obtain 10, 20. 30, 40, 50, 75 and 100 % while distilled water was used as the control. Germination percentage, shoot and root lengths were reduced with increase in concentrations of the S. cordifolia extract. A declined in germination from control was 3.33, 60.0, 72.0, 79.12, 91.26 and 100 % occurred in O. sativa, A. conyzoides, A. gangetica, E. crus-galli, E. colona and P. hysterophorus, respectively. Greater phytotoxicity was observed in P. hysterophorus across the parameters while roots were severely inhibited. Concentrations of Sida crude extract 1.5, 2.25 and 3 g L-1 were sprayed to O. sativa, A. conyzoides, E. crus-galli and P. hysterophorus seedlings at 4, 6 and 8 leaves growth stages at 12 L ha-1 with a hand atomizer. Distilled water was sprayed on control treatments. Data recorded revealed that the leaf extract had effect on plant height, total dry matter and leaf area while slight changes in chlorophyll content and photosynthesis rate were recorded. Transpiration rate and stomatal conductance showed high significant (P ≤0.05) response at different growth stages and it appears more pronounced at low growth stage across species. Phytotoxicity follow order P. hysterophorus > A. conyzoides > O. sativa > E. crus-galli. In the field experiment organo-silicone surfactants (Silwit HS 614) was incorporated with the leaf methanol extract concentrations (3, 6 and 9 g L-1) to improve penetration and enhance performance while distilled water was sprayed on control. We investigated morphological, physiological and biochemical response of A. conyzoides and O. sativa grown under field condition in order to evaluate the degree of phytotoxic effect of foliar spray of S. cordifolia leaf methanol extract. Plant height and shoot dry weight were slightly greater in O. sativa while leaf area decreased and consequently resulted in reduction of growth. Ageratum conyzoides exhibited a significant reduction in chlorophyll contents, carotenoids, chlorophyll fluorescence, peroxidase, catalase and proline. Seven days after the second foliar spray of the S. cordifolia extract leaves yellowing and scorching in A. conyzoides was observed which lasted for a period of 10 days but subsequently subsided, grow and recovered rapidly. The reduction in plant biomass was observed to be related todecreased in chlorophyll content. Activity of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) were stimulated by foliar spray of Sida cordifolia methanol leaf extract (SLE) in a concentration dependent pattern. Ageratum conyzoides maintain comparatively low stress tolerance to SLE compared to O. sativa. Generally phytotoxicity effect of the Sida extract was pronounced in A. conyzoides and P. hysterophorus (Dicots). This could be due the inherent difference, assisted penetration by Surfactant (Silwit 614) and leaf surface area which enable better absorption and penetration of active allelopathins present in the S. cordifolia extract. Ultra Performance Liquid Chromatography revealed a high concentration of rutin while traces of other allelopathins (Quertecin, DL-phenylalanine, P- anisic acid, palmitic acid, stearic acid and syringic and acids) were detected. We suggest further investigations on bioassay in the field on other native weed species to address ecological relevance of our findings, extensive studies on phytochemical analysis of the plant extract including explorations in formulation techniques using surfactants and potency assessment in-situ for their effect on sustainable weed management in agriculture.